STARA Awareness Terhadap Turnover Intention Melalui Job Insecurity Dan Organizational Commitment Dengan Moderator Expectation Retraining - Anugrahaeni, Yulia Putri; Kurniawan, Dediek Tri; Prameka, Adelia Shabrina (Ekonomi Bisnis, 2022)
Research on Smart Technology, Artificial Intelligence, Robotics and Algorithms (STARA) is an interesting topic recently. This study aims to examine the effect of STARA awareness on turnover intention, job insecurity, and organizational commitment. This study used 171 respondents who were obtained through distributing online questionnaires to BRI Regional Office Pekanbaru employees. The data analysis used is SEM-PLS using SmartPLS 3.0 software. This study found that STARA awareness has a significant effect on turnover intention, job insecurity and organizational commitment. This study also shows that job insecurity influences workers' intention to move when they have high job insecurity. However, this study does not proved that organizational commitment had a significant effect on turnover intention. In addition, the results of the study show that job insecurity can affect the effect of STARA awareness on turnover intention, while organizational commitment cannot affect the effect of STARA awareness on turnover intention. Even though, expectation of retraining cannot moderate the effect of STARA awareness on job insecurity.